Analisis Pengaruh Transfer Pricing Pada Perusahaan Yang Mempunyai Hubungan Istimewa Terhadap Laba Bersih PT. Bisi Interasional Tbk. - Yulia Intandani; Fauziyah Rahman; Srikalimah Srikalimah (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to analyze the effect of transfer pricing of a company that has a special relationship on the net profit of PT. Bisi International Tbk. The method used in this research is quantitative with a quantitative descriptive research type. Based on the research results, it shows that transfer pricing has a positive effect net profit on PT. Bisi International Tbk. The higher the transfer pricing, the higher the profit obtained because it can be used to minimize taxes so taxes are smaller. Special relationships have a positive effect net profit on PT. Bisi International Tbk. The higher the special relationship transactions, the higher the transfer pricing will be. Because transfer pricing in companies that have special relationships can reduce the amount of tax charged by the company and indirectly affect the company’s net profit